2019
DOI: 10.3389/fphys.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Training Loads and Perceived Stress in Young Elite University Athletes

Abstract: With increased professionalism in sport there has been a greater interest in the scientific approach to training and recovery of athletes. Applying appropriate training loads along with adequate recovery, is essential in gaining maximal adaptation in athletes, while minimizing harm such as overreaching, overtraining, injury and illness. Although appropriate physical stress is essential, stress for many athletes may come from areas other than training. Stress from may arise from social or environmental pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 60 publications
4
92
0
1
Order By: Relevance
“…The most common timeframe used was a 1-week acute training load and 4-week chronic training load. [9][10][11]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Other timeframes included a 3-day acute load and a 21 daychronic load, 19 or varying timeframes. [37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common timeframe used was a 1-week acute training load and 4-week chronic training load. [9][10][11]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Other timeframes included a 3-day acute load and a 21 daychronic load, 19 or varying timeframes. [37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…38 Colby et al 30 reported, compared to ACWR range of 0.99 to 1.08, ranges of <0.88 (IRR=1.17), 1.08-1.21 (IRR=1.37), and >1.21 (IRR=1.53) resulted in higher incidence of injury, while 0.88-0.99 (IRR=0.60) resulted in a lower incidence when using TD. This same study found that when compared to an above average chronic TD load (81694m over 4 weeks) and moderate 27,30,34,[36][37][38][39] Total [9,10,17,20,21,[23][24][25][26][28][29][30][31][32][33][35][36][37][38]40] ACWR [11,[17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Association Of External Loads and Injury Risks Total Distancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, regular training affects the formation of structural and functional changes in all systems of the human body. However, too much training load and lack of proper regeneration lead to the crossing of the body's adaptive barrier and, as a result, to injury [5]. Extreme sport is also associated with a high psychological burden for athletes [4].…”
Section: Introductionmentioning
confidence: 99%